2016
DOI: 10.2174/1389450116666150506114336
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as a Potential Preventive and Therapeutic Strategy for Cadmium

Abstract: Epidemiological studies provide a growing number of evidences that chronic exposure to relatively low levels of cadmium (Cd), nowadays taking place in industrialized countries, may cause health hazard. Thus, growing interest has been focused on effective ways of protection from adverse effects of exposure to this heavy metal. Because numerous effects to Cd's toxic action result from its prooxidative properties, it seems reasonable that special attention should be directed to agents that can prevent or reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
97
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 190 publications
3
97
0
1
Order By: Relevance
“…Nowadays, the consumption of aronia berries is widely recommended as one of the most abundant sources of compounds having a beneficial influence on the organism, and the richest source among plant materials of anthocyanins, which are characterized by strong antioxidative properties [13,14,[18][19][20][21]. Data provided by Kowalczyk et al [15] and our recent findings [6,22,23] seem to indicate that the consumption of chokeberries and their products may prevent Cd accumulation in the body and its toxic action. Using a female rat model of low and moderate lifetime human exposure to Cd (1 and 5 mg Cd/kg diets, respectively, for up to 24 months), we have revealed that a polyphenol-rich AME may decrease the gastrointestinal absorption and body burden of this xenobiotic (including its accumulation in the liver, kidneys, and bone tissue) [22], as well as significantly prevent disturbances induced by this heavy metal in the bone turnover, and changes in the bone mineral status [23].…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Nowadays, the consumption of aronia berries is widely recommended as one of the most abundant sources of compounds having a beneficial influence on the organism, and the richest source among plant materials of anthocyanins, which are characterized by strong antioxidative properties [13,14,[18][19][20][21]. Data provided by Kowalczyk et al [15] and our recent findings [6,22,23] seem to indicate that the consumption of chokeberries and their products may prevent Cd accumulation in the body and its toxic action. Using a female rat model of low and moderate lifetime human exposure to Cd (1 and 5 mg Cd/kg diets, respectively, for up to 24 months), we have revealed that a polyphenol-rich AME may decrease the gastrointestinal absorption and body burden of this xenobiotic (including its accumulation in the liver, kidneys, and bone tissue) [22], as well as significantly prevent disturbances induced by this heavy metal in the bone turnover, and changes in the bone mineral status [23].…”
mentioning
confidence: 86%
“…Zinc not only stimulates osteoblasts proliferation and differentiation, but it also suppresses osteoclasts differentiation by, among others, antagonizing NF-κB activation [27,33,34]. Polyphenols, due to their ability to bind Cd 2+ [4], may decrease the body burden of Cd and thus protect against the effects of its direct and indirect action, resulting in the improvement of the oxidative/antioxidative balance and bone turnover [6,15,22,23]. It is also necessary to take into consideration that the molecular mechanisms of the beneficial impact of polyphenols on bone tissue metabolism might be related to the ability of these compounds to enhance the production of nitric oxide, which is essential for the induction of new bone formation [35], as well as to induce the nuclear factor erythroid 2-related factor 2 (Nrf2)-mediated antioxidant gene expressions and thereby to decrease the oxidative status [7].…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations